Exploring body image during retirement from elite sport: Perspectives from retired Olympians - Papathomas, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Pressure to be lean for athletic performance gains can lead athletes to adopt an unhealthy preoccupation with body weight and appearance. Athlete body dissatisfaction is prevalent across sports and can lead to disordered eating, negative affect, and poor mental health. Whether body image concerns persist into athletic retirement is a recent focus of research, with insights limited to survey-based data in sub-elite athletic samples. This is the first focused study to explore the meanings elite athletes ascribe to retirement body changes. We recruited 31 retired elite athletes, including 23 former Olympians, to participate in a semi-structured interview. Participants had been retired for between 1 and 7 years (m = 3.9yrs). More than 25 hrs of interview data was transcribed verbatim and subject to a reflexive thematic analysis. We constructed 4 major themes to describe athlete experiences:1) A legacy of body-conscious culture 2) The struggle for "normal", 3) Loss of body as loss of self, 4) Holding on versus moving on. Athletes explained how the body surveillance culture of elite sport echoed into their post-sport lives. An Olympian identity is an embodied identity, so body changes represent a loss of the self. Accepting the inevitability of physical changes in retirement and finding new meanings and identities, eased body dissatisfaction for many, but the process was fraught with difficulties. Athletes` insights may support sport psychologists and elite sport organisations to devise strategies and policies to facilitate adaptation to body changes post-retirement.